2001
DOI: 10.1161/01.hyp.37.3.981
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Hypertension by Irbesartan in Dahl S Rats Relates to Central Angiotensin II Type 1 Receptor Blockade

Abstract: Abstract-Hypertension in Dahl S rats on high-salt intake is in general considered a model of "low-renin hypertension," unresponsive to treatment with blockers of the renin-angiotensin system. However, direct central administration of an angiotensin II type 1 (AT 1 ) receptor blocker prevents both the sympathoexcitation and hypertension caused by high-salt intake in Dahl S rats. In the present study, we tested the hypothesis that chronic peripheral administration of an AT 1 receptor blocker inhibits the salt-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…ANG, chronic peripherally given irbesartan attenuated those to centrally administered ANG (Leenen and Yuan, 2001). Possible brain penetration by orally administered irbesartan and losartan was also explored by a different approach, i.e., by testing inhibition of the dipsogenic response to ANG injected intracerebroventricularly in normotensive and spontaneously hypertensive rats (Polidori et al, 1998).…”
Section: Penetration Into Brainmentioning
confidence: 99%
“…ANG, chronic peripherally given irbesartan attenuated those to centrally administered ANG (Leenen and Yuan, 2001). Possible brain penetration by orally administered irbesartan and losartan was also explored by a different approach, i.e., by testing inhibition of the dipsogenic response to ANG injected intracerebroventricularly in normotensive and spontaneously hypertensive rats (Polidori et al, 1998).…”
Section: Penetration Into Brainmentioning
confidence: 99%
“…76 Recent studies suggest that the systemic administration of the AT1 receptor blockers also act on the AT1 receptors within the brain, thereby reducing blood pressure in hypertensive rats. [80][81][82] The extent of the actions of the AT1 receptor blockers within the brain depends partly on the lipophilicity and pharmacokinetics. 77,78 However, even the hydrophilic AT1 receptor blockers are able to block the AT1 receptors within the blood-brain barrier.…”
Section: Effects Of At1 Receptor Blockers On Oxidative Stress In the mentioning
confidence: 99%
“…Key Words: angiotensin II Ⅲ sympathetic nerve activity Ⅲ nitric oxide Ⅲ interleukins S ubstantial evidence indicates that angiotensin II (Ang II) enhances sympathetic nerve (SNS) activity centrally and peripherally. 1-3 Intracerebroventricular administration of Ang II causes a dose-dependent increase in blood pressure (BP), 4 probably through activation of Ang II type 1 (AT 1 ) receptors localized in the median preoptic nucleus, juxtaventricular neurons of the subfornical organ, organum vasculosum laminae terminalis, 5,6 brain stem, or in preganglionic neurons in the rostral ventrolateral medulla and the intermediolateral column. 7 In a previous study, we showed that intracerebroventricular infusion of Ang II raises BP, renal sympathetic nervous system activity (RSNA), and norepinephrine (NE) secretion from the posterior hypothalamic nuclei (PH).…”
mentioning
confidence: 99%